EFEKTIFITAS SENAM HAMIL TERHADAP KUALITAS TIDUR PADA IBU HAMIL - Chairunnisa " "; Misrawati " "; Febriana " Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Quality of sleep is a situation of sleep that produce an individual freshness and fitness. Pregnancy exercise is a way to improve the quality of sleep of pregnant women, such as pregnancy exercise. The aim of this research is to determine the effectiveness of pregnancy exercise for improving sleep quality during pregnancy. The design of this research is  "quasi experiment" designed by "non-equivalent control group" samples were divided into experiment group and control group. The research was conducted on pregnant women in “Puskesmas Rumbai Pesisir, Pekanbaru”. The total sample are 34 people respondents; 17 people in experiment group and 17 people in control group. Samples were taken by using purposive sampling techniques by noticing  the inclusion criteria. Measuring instruments used is PSQI (Pittsburgh Sleep Quality Index) questionnaire to measure sleep quality. The study uses univariate and bivariate analysis using Mann Whitney and Wilcoxon. The result of univariate analysis show that from 34 respondents, 32 respondents are 20-35 years old (94,1%), 23 respondents are on third trimester (67,6%), and 26 respondents are housewife (76,5%). The result of bivariate analysis show there is a significant reduction of PSQI score during pregnancy in experimental group with p value (0,000) < α (0,05). It means that pregnancy exercise is effective for improving sleep quality during pregnancy. It is recommended for public health center staff to organize prenatal class especially pregnancy exercise regularly. Keywords              : Pregnancy exercise, PSQI, sleep quality